2016
DOI: 10.1124/mol.116.104430
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Driven Pharmacology of Transient Receptor Potential Channel Vanilloid 1

Abstract: The transient receptor potential vanilloid 1 (TRPV1) ion channel is a polymodal receptor that mediates the flux of cations across the membrane in response to several stimuli, including heat, voltage, and ligands. The best known agonist of TRPV1 channels is capsaicin, the pungent component of "hot" chili peppers. In addition, peptides found in the venom of poisonous animals, along with the lipids phosphatidylinositol 4,5-biphosphate, lysophosphatidic acid, and cholesterol, bind to TRPV1 with high affinity to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 113 publications
(149 reference statements)
0
18
0
Order By: Relevance
“…These relationships are fully described in Table II and include a protonation site (R491) [45], capsaicin interacting sites and residues that contribute to the hydrophobic interior of transmembranes domains S1,2, and 4 [60]. Several are involved in voltage or thermal sensing [61,62], and based on mutagenesis studies this Myrcene binding site might also be sensitive to Resiniferatoxin competition [62][63][64]. Residues close to the S4-S5 linker, a key regulatory region for TRPs, are also implicated in binding.…”
Section: Internal Calcium Impact On Myrcene Activation Of Trpv1mentioning
confidence: 99%
“…These relationships are fully described in Table II and include a protonation site (R491) [45], capsaicin interacting sites and residues that contribute to the hydrophobic interior of transmembranes domains S1,2, and 4 [60]. Several are involved in voltage or thermal sensing [61,62], and based on mutagenesis studies this Myrcene binding site might also be sensitive to Resiniferatoxin competition [62][63][64]. Residues close to the S4-S5 linker, a key regulatory region for TRPs, are also implicated in binding.…”
Section: Internal Calcium Impact On Myrcene Activation Of Trpv1mentioning
confidence: 99%
“…We further report that both hypothermia‐inducing TRPV1 antagonists studied (A‐1165901 and AMG7905) potently potentiate the activation of TRPV1 channels by protons in vitro, while potently blocking the capsaicin mode. In view of the pharmacological complexity of TRPV1, it is important to note that neither AMG7905 nor A‐1165901 shows any agonistic activity (ie does not activate the TRPV1 channel by itself, in the absence of any agonists). These new data are in line with the report by Lehto et al who first observed that AMG7905 and AMG8562 potentiated TRPV1 activation by protons in vitro and proposed that such potentiation correlated with the ability of a TRPV1 antagonist to cause hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the hypothermic side effect of TRPV1 antagonists introduces a new concern for drug development. The known hyperthermic side effect is widely acknowledged as a major problem for the development of TRPV1 antagonists . Does the hypothermic effect, with its unknown mechanisms, represent another major problem?…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Given that TRPA1 and TRPV1 receptors appear to have allosteric sites, it is possible that entourage effects are mediated by terpenoid allosteric modulation of cannabinoid actions at these receptors. [20][21][22] In the present study we aimed to assess whether seven terpenoids most commonly found in cannabis have activity at TRPV1 and TRPA1 channels alone, as well as observing whether they modulate the effects of phytocannabinoids and endocannabinoids on these receptors.…”
Section: Introductionmentioning
confidence: 99%